The Effectiveness of Question and Answer Technique in Teaching Reading Comprehension at SMP Negeri 3 Ratahan - Mogea, T (Universitas Negeri Manado, 2019)
This research was conducted with the purpose to develop students’ reading comprehension of descriptive text through question and answer technique. This study is classified as quantitative through pre-experimental design with one group pre-test and post-test design. The population of this research is the students of SMP Negeri 3 Ratahan. It was limited only to the second year studens. There were 30 students. The data were collected through test. The first test is pre-test, the teacher intends to know the students’ reading comprehension without using question and answer technique. The second test is post-test in which the teacher has used question and answer technique in teaching reading comprehension. The result shows that the scores of the students in post-test are higher then those in pre-test. This is shown by the mean score of pre-test which is 5.5 and mean score of post-test which is 7.8 Keywords: Question and Answer Technique; Reading Comprehension